IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM PADA SISTEM PEMBELAJARAN FULL DAY SCHOOL - Jon Helmi (AL-ISHLAH: Jurnal Pendidikan, 2016)
Religion and education have strong relationship. Religion guides human to do good things and leaves bad things. Based on this reason, many schools (private and public school) apply Islamic curriculum and full day system. In full day school, learning process is not merely formal, but also a lot of atmosphere is informal. It is not stuffy. It is fun for students and requires creativity and innovation from teachers. With this system, the length of learning time will not be burden.  It is hoped to create high quality of education